The Effectiveness of Quizizz as Web-Based Learning Media in Teaching Reading Comprehension - Wahyuni, Sri; Styaningsih, Dwi (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study aims at investigating the effectiveness of using Quizizz as a Web- Based Learning Media in Reading Comprehension Learning on recount text. This study used a quasi-experimental research design. Class VIII-J and class VIII-K of a State Junior High School in Kediri were used as research samples. Class VIII K was the experimental group consisted of 34 students and taught by using quizizz, and class VIII J was the control class consisted of 34 students and taught by using Gform. Two set of reading tests were used as pretest and posttest research instruments. The data analysis used the Mann Whitney non-parametric test in SPPS to test the hypothesis because the data was not normally distributed. The result shows that the null hypothesis can be rejected because the significant value obtained is 0.000 < 0.05. Quizizz is effective for teaching reading recount text with a large effect size adopted from the Cohen standard (0.8 ≤ 0.84 ≤ 2.0). According to the findings of this study, it can be concluded that Quizizz is an effective media for teaching recount text. It is also suggested that teachers can apply Quizizz as a learning media so that students are interested.